PEDIATRIC ELBOW COLLATERAL AND ANNULAR LIGAMENT ANATOMY: A CT-BASED CADAVERIC STUDY. Issue 4 (28th April 2020) - Stavinoha, Tyler J.; Cannamela, Peter C.; Ganley, Theodore J.; Shea, Kevin G.
Background: The medial and lateral ligamentous complexes of the elbow provide static restraint to the elbow and serve as important components of posteromedial and posterolateral rotatory instability. Many collateral ligament and medial epicondylar injuries require surgical repair in those with open physes. Little is known about the anatomy of the pediatric elbow and the relationship between these ligaments and physes.Purpose : To evaluate the anterior bundle of the medial collateral ligament complex, lateral ulnar collateral ligament, annular ligament, and relationships to the joint surfaces and physes. Methods: Two cadaveric elbows from a 3 year-old donor were dissected. Collateral and annular ligaments were isolated and left intact at their osseous attachment. Pins were placed at the origins and insertions and CT scans were used to establish precise anatomic relationships. All dissections and measurements were performed by a single orthopedic surgeon with specialization in pediatric sports medicine. Results: The MUCL origin was a mean 4.10 mm distal and anterior to the medial epicondyle, 10.09 mm from the distal humeral articular surface, and 9.01 mm distal to the medial physis. The distal insertion of the MUCL spanned a mean 3.09 mm and was posterior and medial to the sublime tubercle. In the longitudinal axis, the MUCL insertion footprint spanned the tubercle. The origin was a mean 1.20 mm proximal to the sublime tubercle and the distal extent averaged 2.53 mm distal to the tubercle. The center of the MUCL insertional footprint was 0.38 mm distal to the tubercle. The center of the MUCL was 3.87 mm from the olecranon articular surface. The annular ligament had consistent medial and lateral attachments to the ulna. Distance from the annular ligament attachments to the tip of the coronoid averaged 4.6 mm (4.46 & 4.74 lateral and medial for left; 4.80 & 5.27 lateral and medial for right). The LUCL origin was distal and anterior to the lateral epicondyle. It was 3.43 mm from the lateral epicondyle, 7.51 mm from the articular surface and 0.74 mm distal to the physis. Conclusions: This study is the first to describe anatomy of the elbow collateral and annular ligaments in pediatric cadaveric specimens, through a reliable, CT-based identification method. Knowledge of the precise ligamentous attachments and relationships to the physis and to the joint surface is important for reconstructive procedures. A better understanding of these relationships may assist with surgical planning that preserves adjacent physeal growth regions.